The Influence of Post Frequency and Type of Platform Used on Follower Interest Levels - Azzahra, Nabila; Utami, Bulan Purnama; Arrafi, Adamsyam; Handayani, Vitri Aprilla (JURNAL SINTAK, 2024)
This study examines the influence of social media platform types and posting frequency on the level of follower interest in a content creator's account. The analysis results show that the type of platform (Instagram or TikTok) does not have a significant impact on follower interest. However, posting frequency is proven to have a substantial influence, with weekly frequency showing the most positive impact. The interaction between platform type and posting frequency does not demonstrate a significant effect. These findings suggest that content creators can focus on adjusting their posting frequency, particularly with a weekly schedule, to increase follower interest, without needing to worry about choosing between Instagram or TikTok platforms.